2019
DOI: 10.1002/ece3.5603
|View full text |Cite
|
Sign up to set email alerts
|

Widespread hybridization in the introduced hog deer population of Victoria, Australia, and its implications for conservation

Abstract: In Australia, many species have been introduced that have since undergone drastic declines in their native range. One species of note is the hog deer (Axis porcinus) which was introduced in the 1860s to Victoria, Australia, and has since become endangered in its native range throughout South‐East Asia. There is increased interest in using non‐native populations as a source for genetic rescue; however, considerations need to be made of the genetic suitability of the non‐native population. Three mitochondrial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 74 publications
3
22
0
Order By: Relevance
“…Hybridization has been found to be relatively common between ungulate species, in large part due to detection using increasingly complex nuclear datasets, and often in combination with mtDNA that can highlight discordant genealogies, a common signature of interspecific gene flow (Hill, Linacre, et al, 2019;Hill, Havird, et al, 2019;Iacolina et al, 2019) Given the consistency of these results, we hypothesize that some sorting mechanism exists within the exome where critical functional genomic elements must remain true to species assignment through inheritance, and unfit allele combinations as a result of hybridization are purged. If so, this would indicate strong directional selective pressure on hybrids.…”
Section: Contemporary Hybridization Dynamicsmentioning
confidence: 95%
“…Hybridization has been found to be relatively common between ungulate species, in large part due to detection using increasingly complex nuclear datasets, and often in combination with mtDNA that can highlight discordant genealogies, a common signature of interspecific gene flow (Hill, Linacre, et al, 2019;Hill, Havird, et al, 2019;Iacolina et al, 2019) Given the consistency of these results, we hypothesize that some sorting mechanism exists within the exome where critical functional genomic elements must remain true to species assignment through inheritance, and unfit allele combinations as a result of hybridization are purged. If so, this would indicate strong directional selective pressure on hybrids.…”
Section: Contemporary Hybridization Dynamicsmentioning
confidence: 95%
“…However, in effect only the first three species are hunted because there are no wild populations of chital and rusa deer now present in Victoria. Hog deer (Axis porcinus) (Hill et al 2019) can only be hunted during April and only one male and one female may be taken by each hunter during the regulated season. Limited balloting allows selected hunters to take small numbers outside the April season.…”
Section: Introductionmentioning
confidence: 99%
“…The 'Snake Island' cluster, comprising all samples from Snake Island as well as individuals from Stratford and Loch Sport, showed very strong genetic differentiation to all other sampling sites in Victoria. No private alleles were observed in the Snake Island population, and previous research did not reveal any differences in mitochondrial or nuclear sequences when compared to other populations (Hill et al 2019). This observed genetic difference may be due to Snake Island being one of the initial hog deer release sites, undergoing a separate founder event and consequent genetic drift due to the long-lasting isolation from the mainland populations.…”
Section: Genetic Structurementioning
confidence: 47%
“…Assessment of the impacts of sustained harvesting in sites managed as game reserves, and historical hybridisation between hog deer and chital are also of interest, particularly in measurements of genetic diversity. Previous research has shown that hog deer hybridised with chital very early in the initial introduction of the species, with all hog deer tested comprising a chital mitochondrial haplotype, and analysis of mitochondrial DNA revealed local populations of hog deer to be monomorphic at the D-loop region (Hill et al 2019), suggesting diversity is very low in Victorian hog deer. The low levels of diversity at this mitochondrial region are likely due to founder effects and may be reflective of chital diversity at the time of hybridisation rather than hog deer.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation